ANALISIS PENDAPATAN DAN SISTEM PEMASARAN PADI ORGANIK DAN ANORGANIK DI KABUPATEN PRINGSEWU - Astuti, Fitria Kusuma; Haryono, Dwi; Nugraha, Adia (Lampung University, 2020)
The aims of this research are to analyze income, comparison of income, and marketing effeciency of organic and inorganic rice farming in Pringsewu District. This research was conducted in Fajaresuk Village Pringsewu Subdistrict, Pringsewu District using a survey method Data were collected from August to September 2017. The sample size in research were 14 organic rice farmers, 25 inorganic rice farmers, 15 marketing respondents including 1 member of Sejahtera Farmer Group, 9 rice merchants, and 5 millers based on rice marketing flow (snowball). The data were analyzed using income, comparison of income, and marketing analyses. The results of study showed that organic rice farming income bigger than inorganic rice farming income. There is a significant difference between organic and inorganic rice farming income. The marketing of organic rice is more efficient than inorganic rice.Keywords: income, inorganic rice, marketing, organic rice